2016
DOI: 10.1021/acs.jpcc.5b11764
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Nuclear Dynamics of Doped Conjugated Polymers

Abstract: Infrared-active vibrational (IRAV) modes are specific optical fingerprints to probe the density, dynamics, and spatial distribution of polarons in π-electron conjugated polymers. So far, the description of IRAV mode activation and selection rules, resulting from the local breaking of spatial symmetry induced by charge carriers, has been restricted to phenomenological lattice-dynamics models. Overcoming the classical picture, here we combine first-principles calculations with vibrational spectroscopy to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 63 publications
4
41
1
Order By: Relevance
“…Whilst some of them can be traced back to ground state modes, the distinct assignment to polaron-related modes has recently been invoked for the most prominent features. 10,11,16 Of the smaller features, some shift to lower energy (e.g. at 0.102 eV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst some of them can be traced back to ground state modes, the distinct assignment to polaron-related modes has recently been invoked for the most prominent features. 10,11,16 Of the smaller features, some shift to lower energy (e.g. at 0.102 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Also this classical explanation has recently been contested and it was suggested that pronounced vibrational signals should be considered as related to polarons instead of the ground state of the polymer. 10,11 The low energy signatures of polymer polarons have lately moved back into the focus of research interest as a means to extract information about the chain conformation in the environment of the charge carrier. The groups of Schwartz 12 and Salleo, 13 for example, studied the spectra of doped films of P3HT to investigate the location of doping-induced charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The S 2 ← S 1 mid-IR absorption observed here bears some resemblance with the low-energy polaron bands observed in the electronic absorption spectra of open-shell cations of conjugated oligomers and in doped conjugated polymers, as the latter report on the delocalization of the charge across the chain 62,63 . Charge localization breaks the symmetry leading to the transformation of Raman active modes into infrared-active vibrations (IRAVs) [64][65][66] .…”
Section: Discussionmentioning
confidence: 99%
“…Common experiments used to validate electronic simulations include ultraviolet photoelectron spectroscopy (UPS) [43,44], ultraviolet-visible spectroscopy (UV-vis) [45][46][47] and infrared spectroscopy (IR) [46,48,49]. Each experiment validates a different observable of the DFT calculation.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…This is difficult to reproduce with DFT; it is difficult to assign meaning to excited orbitals in DFT, as the theorems of DFT hold for the ground state only [50]. IR spectroscopy measures symmetry allowed molecular vibrations, which can be accurately simulated by finding the eigenvalues of the a matrix of interatomic force constants [48,49].…”
Section: Density Functional Theorymentioning
confidence: 99%